Random sampling and large deviations - McGurk, Brian (Trinity College (Dublin, Ireland). School of Mathematics, 2001)
In this thesis, we are concerned with the effect of randomly sampling a stochastic process. We consider two stochastic processes: the underlying process, {Xt}tεT and the observation process {Tn}nεN, a strictly increasing process taking values in T . The process of interest is generated by sampling the underlying process at the times specified by the observation process, Yn:=XTn
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin